Gods and men of Huamanga - Szeminski, Jan (1982)
This text is the result of the joint work of the authors with the students of the Text Analysis course that took place at the National University of San Cristóbal de Huamanga during the first semester of the academic year of 1981. After analyzing some examples of Andean myths, we asked the students to interview each one a person linked to the Andean world, giving extremely general guidelines so that they could bring information related to mythical thought. The students -all anthropology- were for the most part in the 200 series (Second year) with no interview experience and for many the course was their first serious contact with anthropology. They generally did not have a tape recorder, and sometimes instead of transcribing the text on the tape, they wrote down their own translation because they did not master Quechua writing or because they mishandled this language.